Implementasi Kesetaraan Gender Dan Pemanfaatan Teknologi (Aplikasi Lapor) Bagi Digital Society Di Ruang Lingkup Kabupaten Banyuasin, Kecamatan Banyuasin III, Kelurahan Pangkalan Balai - Faila Sufa Marhamah; M. Febrianza; Marleni; Putriyanti (Yayasan Kawanad, 2024)
This Community Service Journal aims to describe the implementation of gender equality within the scope of Banyuasin Regency, Banyuasin III District, Pangkalan Balai Village. The topic of gender equality was chosen based on direct observations in the field and is an interesting topic because issues regarding gender are currently being widely discussed everywhere, be it on social media, mass media and other media. The research method uses qualitative research methods with data collection techniques, namely through observation, in-depth interviews and documentation, while data analysis techniques use taxonomic data analysis techniques. The implementation of gender equality in this research has not yet been fully realized due to several factors, including a lack of budget, inadequate community resources and the government's role which is still not very big on issues regarding gender equality.